Analysis of the Frequency of Academic Staff and Students` Use of Information and Communication Technology (ICT) in Katsina State College of Education - A.E., Mbaba (Information Management and Business Review, 2012)
The paper analyze the frequency of academic staff and students use of information and communication technology Ict in Katsina State College of Education, it explore the ability of staff and students in computer application 114 academic staff and 1995 students were engaged in the study. A survey research design was used; the data collected was analyzed using percentage to present the responses. 4 point Likert-scale was used, while a mean of 2.50 was adopted to determine the higher and lower participation in the use of ICT and ability in computer application. The finding show that the use of ICT in the College is high [m=2.78 higher than m=2.50]. The study also indicated that the academic staff are more competent in the use of wide range of computer applications than students are [m=3.08and 2.56 respectively] the study reveals that the staff and students actually engaged in the use of ICT almost on a daily basis for both school learning and individual use. The researchers therefore recommend that this study should be carried out in all the tertiary institutions in Nigeria to clarify the uncertainty of the frequency of ICT use in Nigeria schools.